2010
DOI: 10.1128/jvi.01843-09
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Burkholderia cepacia Complex Phage KS9 gp41 Identifies the Phage Repressor and Generates Lytic Virions

Abstract: The Burkholderia cepacia complex (BCC) is made up of at least 17 species of Gram-negative opportunistic bacterial pathogens that cause fatal infections in patients with cystic fibrosis and chronic granulomatous disease. KS9 (vB_BcenS_KS9), one of a number of temperate phages isolated from BCC species, is a prophage of Burkholderia pyrrocinia LMG 21824. Transmission electron micrographs indicate that KS9 belongs to the family Siphoviridae and exhibits the B1 morphotype. The 39,896-bp KS9 genome, comprised of 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
65
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(65 citation statements)
references
References 47 publications
0
65
0
Order By: Relevance
“…This situation may be analogous to the behavior of phage lambda int mutants, which are able to form abortive lysogens that give rise to sensitive cells upon subculture (19,21). In a study of a known temperate B. cenocepacia phage, KS9, only 18% of the phage-insensitive strains isolated following phage challenge were true lysogens, the remainder becoming insensitive presumably by some other mechanism (49). Phages Bcep22 and BcepIL02 may be a more extreme version of this behavior, in which lysogen formation, if it occurs, is below the rate of bacterial mutation to phage insensitivity.…”
Section: Vol 193 2011mentioning
confidence: 99%
“…This situation may be analogous to the behavior of phage lambda int mutants, which are able to form abortive lysogens that give rise to sensitive cells upon subculture (19,21). In a study of a known temperate B. cenocepacia phage, KS9, only 18% of the phage-insensitive strains isolated following phage challenge were true lysogens, the remainder becoming insensitive presumably by some other mechanism (49). Phages Bcep22 and BcepIL02 may be a more extreme version of this behavior, in which lysogen formation, if it occurs, is below the rate of bacterial mutation to phage insensitivity.…”
Section: Vol 193 2011mentioning
confidence: 99%
“…13 ϕH111-1 was able to infect all 13 strains tested (Table S1), providing further evidence that this phage may be an appropriate candidate for therapeutic use (particularly if the lysogeny module were deleted). 8 Excluding B. cenocepacia, the ϕH111-1 host range was found to be relatively narrow as only B. multivorans ATCC 17616 and C5274 were susceptible to phage infection from a panel of 18 other Burkholderia strains tested (representing 8 additional BCC species) ( Table S1).…”
Section: B Cenocepacia H111 Prophage Screening and Isolationmentioning
confidence: 99%
“…4 Although the therapeutic use of temperate phages is generally discouraged, the limited availability of obligately lytic BCC phages has necessitated the use of confirmed, putative, or modified temperate phages for several in vivo efficacy studies. [6][7][8] The use of such phages against Burkholderia is arguably safer than it is against many other pathogens because virulence factors in this genus have not been discovered to be encoded by temperate phages. 2 One of the challenges of prophage identification is the differentiation of inducible prophages from defective prophage remnants, a distinction with both evolutionary and practical implications.…”
Section: Introductionmentioning
confidence: 99%
“…In a type of coevolutionary arms race, phages can rapidly adapt to counter improvements in bacterial resistance, which is in direct contrast to the long development time required for new static chemical antibiotics (21). Recent studies exploring the treatment of Bcc infections via phage therapy have demonstrated promise (22)(23)(24)(25)(26), including our recent study showing Bcc phage efficacy in a mouse infection model (26).…”
mentioning
confidence: 99%